Legal Certainty of Ownership and Transfer of Rights to Alternate Rice Field Land in Kerinci Regency - Qurratul Aini; M.Hasbi; Syofiarti (Dinasti Research, 2025)
The Kerinci indigenous people apply a system of land tenure of alternate rice fields that are inherited matrilineally. However, this system faces obstacles in legal certainty, especially related to the transfer of rights and land registration. This study aims to analyze the pattern of control, legal certainty, and dispute resolution mechanism in the system. The method used is empirical juridical with an analytical descriptive approach. The results show that although the rotational rice field system is still in effect, the absence of ownership certificates hinders legal certainty, while dispute resolution still relies on customary institutions. Harmonization of customary law and agrarian law is needed to improve legal protection for the Kerinci indigenous people.